A case series of severe perineal lacerations during normal childbirth - Nahid Jahani Shourab; Masoumeh Mirteimouri; Robab Latifnejad Roudsari (Mashhad University of Medical Sciences, 2018)
Introduction: Severe perineal tears during delivery decrease maternal health and satisfaction. This is a challenge for promotion and acceptance of normal vaginal birth. Therefore, this study was performed with aim to identify the risk factors associated with severe perineal tears during normal vaginal delivery. Methods: This was a case-series study which was performed by reviewing medical records and interviewing with women who gave birth from 20th April to 25th December 2016 at Omolbanin Hospital, Mashhad, Iran and had third and fourth degree perineal lacerations. Data extracted from patients' medical records included demographic and childbirth-related data (number of parity, the length of the first and second stage of labour, frequency and duration of  uterine contractions, prescribed medications in labour, birth attendant, mode of delivery, degree of perineal tear, method of perineal repair and neonatal weight) that was recorded in related forms. Interviews were conducted within the first year after childbirth following telephone invitation, focusing on women's chief complains. Descriptive statistics were used for data analysis. Results: Out of the seven Iranian patients studied, four cases (57.2%) were multiparous and three cases were primiparous. The most risk factors associated with perineal lacerations included 6 cases of induction by oxytocin (85.7%), 3 cases of gestational diabetes (42.8%), 3 cases of postdate pregnancy (42.8%) and 2 cases of macrosomia (28.50%). The delivery of only one case was done by the skilled stuff of labor and the others were accomplished by medical and midwifery students. In 6 cases (%85.7), more than one risk factor was seen. The most common postpartum complication was gas incontinence. Conclusion: Labor induction with oxytocin, gestational diabetes, and postdate pregnancy are the most common risk factors associated with severe perineal tears during normal delivery. The majority of women suffer of gas incontinence, even after successful repair of perineal lacerations.